Adolescent neurobiological susceptibility to social context. (June 2016) - Schriber, Roberta A.; Guyer, Amanda E.
Highlights: We propose a framework, adolescent neurobiological susceptibility to social context. This framework pivots about brain-based individual differences in social sensitivity. Adolescent brain indices may moderate the effect of social context on development. Neuroimaging work on social context, the adolescent brain, and outcomes is reviewed. We suggest that brain measures be used to index neurobiological susceptibility. Abstract: Adolescence has been characterized as a period of heightened sensitivity to social contexts. However, adolescents vary in how their social contexts affect them. According to neurobiological susceptibility models, endogenous, biological factors confer some individuals, relative to others, with greater susceptibility to environmental influences, whereby more susceptible individuals fare the best or worst of all individuals, depending on the environment encountered (e.g., high vs. low parental warmth). Until recently, research guided by these theoretical frameworks has not incorporated direct measures of brain structure or function to index this sensitivity. Drawing on prevailing models of adolescent neurodevelopment and a growing number of neuroimaging studies on the interrelations among social contexts, the brain, and developmental outcomes, we review research that supports the idea of adolescent neurobiological susceptibility to social context for understanding why and how adolescents differ in development and well-being. We propose that adolescent development is shaped by brain-based individual differences in sensitivity to social contexts – be they positive or negative – such as those created through relationships with parents/caregivers and peers. Ultimately, we recommend that future research measure brain function and structure to operationalize susceptibility factors that moderate the influence of social contexts on developmental outcomes.